On Some Problems of James Miller - Bhowmik,B (Universidad de La Frontera. Departamento de Matemática y Estadística., 2010)
We consider the class of meromorphic univalent functions having a simple pole at and that map the unit disc onto the exterior of a domain which is starlike with respect to a point . We denote this class of functions by . In this paper, we find the exact region of variability for the second Taylor coefficient for functions in . In view of this result we rectify some results of James Miller.